The Stylistic Analysis of Mulla Manochehr Kolivand's Book of Poetry - Yosofali Beiranvand; Aliashraf Mirzai (پژوهشنامه ادبیات کردی)
Mulla Manochehr Koulivand was one of the Lak poets who had a language close to Persian. He lived during the Qajar period. In this research, our aim is to study Mulla Manochehr's poems based on stylistic levels by descriptive-analytical method. After analyzing his poems, the following results were achieved: 1- Linguistic level: a) Phonetic level: Mulla Manouchehr used prosody metre instead of syllabic metre and used Arabic, Persian and Laki rhymes. The radifs of his poetry are more Laki. Various types of puns, riming proses and phonemes are seen in his poetry. b) Lexical level: sometimes Mulla Manochehr removes the final vowels "h, t, b" and middle and final "d" from the words. Changing the phoneme "z" to "zh" which is common in Lakhi is also found in Mulla's poems. Old Laki words that have little use now can be seen in his poems. He has used a lot of Arabic words. There are the low number of Turkish words as well as old Persian words in poems of Mullah. c) Syntactic level: Mulla Manochehr has used Laki verbs more than the verbs of other languages. He has used the equivalent of Laki "this" and "that" and I personal pronoun of Laki. 2- Literary level: simile, trop, kenning, metaphor, allusion, implication, symmetry, exaggeration, oxymoron and conglobatio are also seen in poems of Mulla Manochehr. 3- Intellectual level: The themes of Mulla's poems are description of old age, praise, description of spring, description of spiritual wine, happiness and description of nature.